HIV BROADLY NEUTRALIZING ANTIBODIES: TAKING GOOD CARE OF THE 98% - Sok, Devin (Immunity, 2016)
In this issue of Immunity, Huang et al. describe an exceptionally broad and potent neutralizing antibody to HIV. This antibody, N6, is capable of neutralizing up to 98% of global isolates with a potent median IC(50) of 0.04 μg/ml, making it the current “best-in-class” for bnAbs targeting the CD4 binding site.